PENERAPAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN PADA SISWA KELAS IV SD NEGERI 4 KUWAYUHAN - Kuswandari, Diah; Suhartono, Suhartono; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The use of experiential learning model in improving story-writing skill for fourth grade students of SD Negeri 4 Kuwayuhan. The objectives of this research is to improve story-writing skill for fourth grade students of SD Negeri 4 Kuwayuhan in the academic year of 2016/2017 through the use of experiential learning model. This research is a collaborative Classroom Action Research (CAR). Subjects of the research were 24 students of fourth grade and its teacher. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptiveanalysis consisting of data reduction, data display, and drawing conclusion or verification. The results of this research show that the use of experiential learning model can improve story-writing skill for fourth grade students of SD Negeri 4 Kuwayuhan in the academic year of 2016/2017.Keywords: Experiential Learning, writing skill, story-writing Abstrak: Penerapan Model Experiential Learning untuk Meningkatkan Keterampilan Menulis Karangan pada Siswa Kelas IV SD Negeri 4 Kuwayuhan. Tujuan penelitian ini adalah untuk meningkatkan keterampilan menulis karangan pada siswa kelas IV SD Negeri 4 Kuwayuhan melalui penerapan model Experiential Learning. Penelitian ini merupakan penelitian tindakan kelas kolaboratif. Subjek penelitian ini adalah guru dan siswa kelas IV yang berjumlah 24 siswa. Teknik pengumpulan data pada penelitian ini, yaitu: observasi, wawancara, dan tes. Validitas data yang digunakan, yaitu triangulasi sumber dan triangulasi teknik. Analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan model Experiential Learning dapat meningkatkan keterampilan menulis karangan siswa.Kata kunci: Experiential Learning, keterampilan menulis, menulis karangan